PENGUKURAN DAYA LASER CO2 DAN LASER DPSS SERTA PENGAMATAN BEAM PROFILER SINAR LASER DPSS DAN LASER He-Ne MENGGUNAKAN CCD - Helen Martina Manurung (Saintia Fisika, 2013)
This research has done measuring the power by varying the current of laser CO2 and laser DPSS, observation the beam profiler of laser beam DPSS and laser beam He-Ne and observation the spectrum wavelength of laser DPSS and laser He-Ne. In this case of measuring the power by varying the current of laser CO2 and laser DPSS, the measuring has done more than once in order to concluded how the stability of the power that produced by each of the laser. The result of this measuring is laser DPSS produced the power more stable than the laser CO2 but the laser CO2 produced the power more bigger than the laser DPSS. In this research, the observation the beam profiler of laser beam DPSS and laser beam He-Ne by using CCD which is the censor to record the figure of light emited by the laser and then transmitted to the computer and processed by using software Laser Beam Analyzers to show the type of 2 dimension and 3 dimension of the laser. After that doing this observation, the conclusion are the distance of the CCD form the laser DPSS is 32 cm and the diameter of the laser beam is 3,673 mm and the distance of the CCD from the laser He-Ne is 10 cm and the diameter of the laser beam is 4,451 mm. In this research also made the observation of the spectrum wavelength of the laser by using spectrometer HR4000. Kata kunci : Laser CO2, Laser DPSS, Laser He-Ne, CCD